1999
DOI: 10.1021/jp984378j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Iron and Manganese Species in Iron- and Manganese-Promoted Sulfated Zirconia

Abstract: The structural analyses of Fe, Mn−SO4 2-/ZrO2 (FMSZ), Fe−SO4 2-/ZrO2 (FSZ), Mn−SO4 2-/ZrO2 (MSZ), and Fe−Mn/ZrO2 (FMZ) were carried out by means of XAFS, XRD, and Raman spectroscopy. Local structure around Fe and Mn of each catalyst, which were at a working state for n-butane isomerization and in vacuo, were studied by in situ XAFS. The valence of the Fe atom of all the catalysts was invariantly trivalent. Coordination environment around Fe of all the catalysts was quite similar to each other. Fe atoms are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 39 publications
7
53
2
Order By: Relevance
“…Srinivasan et al, 17 Hino and Arata, 34 and Tábora and Davis 3 concluded that Fe was present as (small clusters or rafts of) Fe 2 O 3 , and it was stated 3 that there is no isomorphous substitution of Fe into tetragonal zirconia. According to Tanaka et al 4 and Yamamoto et al, 5 Fe 3+ formed an interstitial-type solid solution with ZrO 2 . Miao et al 19 suspected that promoters may be present in the form of oxide solid solutions or highly dispersed on the surface.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Srinivasan et al, 17 Hino and Arata, 34 and Tábora and Davis 3 concluded that Fe was present as (small clusters or rafts of) Fe 2 O 3 , and it was stated 3 that there is no isomorphous substitution of Fe into tetragonal zirconia. According to Tanaka et al 4 and Yamamoto et al, 5 Fe 3+ formed an interstitial-type solid solution with ZrO 2 . Miao et al 19 suspected that promoters may be present in the form of oxide solid solutions or highly dispersed on the surface.…”
Section: Introductionmentioning
confidence: 95%
“…Yamamoto et al 5 detected MnSO 4 in sulfate-containing and Mn 2 O 3 in sulfate-free samples. Scheithauer et al 23 reported well-dispersed Mn2+.…”
Section: Introductionmentioning
confidence: 99%
“…52 It is not clear whether sulfate is directly associated with the promoters. Yamamoto et al proposed that Mn is present as MnSO 4 on the surface, 53 Scheithauer et al 54 and Tábora and Davis 55 reported small Fe 2 O 3 rafts on the surface. However, our preparation method produces materials with the majority of Mn and a significant fraction of Fe incorporated into the zirconia lattice.…”
Section: Effect Of Promotersmentioning
confidence: 99%
“…The XRD patterns of sulphated zirconia show peaks assigned to both the tetragonal phase at 2θ (30.2°, 35.4°, 50.2°, 60.3°) (JSPDS file 00-014-0534: zirconium oxide) and diffraction lines around 2θ (43.8°, 62.9°, 75.1°) (JSPDS file 01-086-1449ZrO 2 ) of the monoclinic phase of zirconia. 1,39 By using the Scherrer's equation, the average size of sulphated zirconia was estimated to be 40 nm.…”
Section: Resultsmentioning
confidence: 99%